The Use of ISSR and RAPD Markers for Genetic Diversity among South Tunisian Barley. (3rd January 2012) - Guasmi, Ferdaous; Elfalleh, Walid; Hannachi, Hédia; Fères, Khadija; Touil, Leila; Marzougui, Nidhal; Triki, Tebra; Ferchichi, Ali
Abstract : Random amplified polymorphic DNA (RAPD) and intersimple sequence repeat (ISSR) were assayed to determine the genetic diversity of 80 barley specimens from South Tunisia. The ISSR primers showed variation in the percentage of polymorphism, band informativeness (Ib), and resolving power (Rp). The percentage of polymorphism is 66.67%, the average Ib ranged from 0.24 to 0.39, while Rp ranged from 0.74 to 1.16. In RAPD analysis, three primers yielded a total of 17 scorable bands, which are all polymorphic. The three polymorphic primers exhibited variation with regard to average band informativeness (AvIb) and resolving power (Rp). RAPD and ISSR marker systems were found to be useful for the genetic diversity among the barley specimens. The two dendrograms obtained through these markers show different clustering of 80 barely specimens, but we noted that some clusters were similar in some cases. A poor correlation (r = 0.12 ) was found between both sets of genetic similarity data, suggesting that both sets of markers revealed unrelated estimates of genetic relationships. Therefore, the ISSR and RAPD molecular markers show two genetic grouping of studied barely specimens.